2018
DOI: 10.1002/ece3.3874
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny, habitat together with biological and ecological factors can influence germination of 36 subalpine Rhododendron species from the eastern Tibetan Plateau

Abstract: The reproductive stages of the life cycle are crucial in explaining the distribution patterns of plant species because of their extreme vulnerability to environmental conditions. Despite reported evidence that seed germination is related to habitat macroclimatic characteristics, such as mean annual temperature, the effect of this trait in controlling plant species distribution has not yet been systematically and quantitatively evaluated. To learn whether seed germination can predict species distribution along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…Importantly, the findings demonstrated that genetic differentiation was the primary factor driving this variation in xylem embolism resistance in these ten species, considering that they were grown in a homogeneous nursery. These results provide a theoretical foundation for understanding the extensive distribution of Rhododendron species across elevations ranging from a few hundred meters to 5500 m above sea level (Wang et al, 2018; Wang et al, 2014) and their species diversity within alpine ecosystems (Xia et al, 2021). Moreover, this variability can guide the selection of Rhododendron species that are better adapted to different arid habitats based on their leaf xylem vulnerability to embolism.…”
Section: Discussionmentioning
confidence: 94%
“…Importantly, the findings demonstrated that genetic differentiation was the primary factor driving this variation in xylem embolism resistance in these ten species, considering that they were grown in a homogeneous nursery. These results provide a theoretical foundation for understanding the extensive distribution of Rhododendron species across elevations ranging from a few hundred meters to 5500 m above sea level (Wang et al, 2018; Wang et al, 2014) and their species diversity within alpine ecosystems (Xia et al, 2021). Moreover, this variability can guide the selection of Rhododendron species that are better adapted to different arid habitats based on their leaf xylem vulnerability to embolism.…”
Section: Discussionmentioning
confidence: 94%
“…The seed germination stage is sensitive to the external environment; there are many factors that affect the seed germination stage, and temperature is one of the main environmental factors that determine seed germination [7]. When the temperature exceeds a certain limit, the water absorption and oxygen intake of seeds is limited [8], significantly affecting germination time, slowing the germination rate and reducing the germination potential [9].…”
Section: Effect Of High-temperature Stress On the Seed Germination Of...mentioning
confidence: 99%